2015
DOI: 10.1080/07481187.2015.1115787
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved families and the coronial response to traumatic workplace fatalities: Organizational perspectives

Abstract: Work remains a significant source of illness, injury, and death in developed countries. In Australia, for example, over 2,000 people die from work-related causes each year, with heavy social, economic, and personal costs (Safe Work Australia, 2013a ). Most die as a result of work-related disease. However, many die from trauma. In 2012, 223 workers were fatally injured in Australia and in the United States the figure was 4,383 (Bureau of Labor Statistics, 2014 ; Safe Work Australia, 2013b ). Apart from the imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…Analyses of the extent to which the reports from coronial investigations identify root causes or systemic failures as contributors to fatal work incidents conclude that coroners do not always extend their investigation beyond the immediate cause of death to examine possible systemic failures (Cooke & Lingard, 2011; Hopkins et al., 1992). The present findings reinforce earlier research on the coronial system and fatal work incidents which, while identifying positive changes, highlights significant limitations in both resourcing and the practices and expertise of coroners (Matthews et al., 2016).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Analyses of the extent to which the reports from coronial investigations identify root causes or systemic failures as contributors to fatal work incidents conclude that coroners do not always extend their investigation beyond the immediate cause of death to examine possible systemic failures (Cooke & Lingard, 2011; Hopkins et al., 1992). The present findings reinforce earlier research on the coronial system and fatal work incidents which, while identifying positive changes, highlights significant limitations in both resourcing and the practices and expertise of coroners (Matthews et al., 2016).…”
Section: Discussionsupporting
confidence: 89%
“…In Australia, each jurisdiction has its own Coroners Act that governs the holding of inquests. With the exception of Tasmania, inquiries are not mandatory for fatal work incidents (Matthews, Fitzpatrick, Quinlan, Ngo, & Bohle, 2016). It is the coroner’s decision as to whether an inquest is held or whether an administrative finding with a simple narrative of the cause of the death (chamber report) is all that is required (Hands, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many participants in this study reported feeling better prepared for, and less anxious about, inquests, in cases where they were provided timely access to evidence in the brief and referrals to support services. These results accord with research specifying the benefit of timely referrals and allowing families “first hand” access to the evidence to enable full participation in proceedings, to minimise surprises, and to elucidate the scope of the investigation (Victorian Parliament Law Reform Committee, 2006; Matthews et al, 2016). The present study extended the coronial literature by describing particular aspects of support services that were helpful.…”
Section: Discussionsupporting
confidence: 71%
“…Third, the study was part of a wider project that included detailed interviews with regulatory agencies (inspectorates, workers’ compensation authorities, coroners and police) and institutions (insurers, unions, employers, and lawyers) who deal with families following a workplace death. Their views provided a detailed understanding of how institutions respond to sudden work deaths, including the provision of information, counseling, financial, and other supports (26, 98). For example, the families of self-employed workers—a growing segment of the workforce in the gig economy—are largely denied access to workers’ compensation, and this financial burden causes considerable concern and financial distress, possibly exacerbating the mental anguish that families experience (28).…”
Section: Discussionmentioning
confidence: 99%